2013
DOI: 10.1371/journal.pone.0062941
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Accumulation of Copper and Lead in Amaranth (Amaranthus paniculatus), Indian Mustard (Brassica juncea) and Sunflower (Helianthus annuus)

Abstract: BackgroundSoil contamination by copper (Cu) and lead (Pb) is a widespread environmental problem. For phytoextraction to be successful and viable in environmental remediation, strategies that can improve plant uptake must be identified. In the present study we investigated the use of nitrogen (N) fertilizer as an efficient way to enhance accumulation of Cu and Pb from contaminated industrial soils into amaranth, Indian mustard and sunflower.Methods/Principal FindingsPlants were grown in a greenhouse and fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…The findings show that application of higher levels of both N-fertilizer and EDTA are likely to enhance the accumulation of Cd in the shoots of Vetiver grass whereas the opposite was found with elemental S. Notwithstanding, the trend for Pb accumulation was in the following order of EDTA (25EDTA) > N-fertilizer >> elemental S among all treatments. The application of higher levels of EDTA and N-fertilizer could have probably increased Pb accumulation in the shoots of Vetiver grass, as similar trends have been reported previously by Nascimento et al (2006), Chiu et al (2006) and Rahman et al (2013). Although higher Pb accumulation was recorded with the application of N-fertilizer in the shoots, relatively all levels of N-fertilizer treatments displayed approximately similar accumulation of Pb.…”
Section: Resultssupporting
confidence: 86%
“…The findings show that application of higher levels of both N-fertilizer and EDTA are likely to enhance the accumulation of Cd in the shoots of Vetiver grass whereas the opposite was found with elemental S. Notwithstanding, the trend for Pb accumulation was in the following order of EDTA (25EDTA) > N-fertilizer >> elemental S among all treatments. The application of higher levels of EDTA and N-fertilizer could have probably increased Pb accumulation in the shoots of Vetiver grass, as similar trends have been reported previously by Nascimento et al (2006), Chiu et al (2006) and Rahman et al (2013). Although higher Pb accumulation was recorded with the application of N-fertilizer in the shoots, relatively all levels of N-fertilizer treatments displayed approximately similar accumulation of Pb.…”
Section: Resultssupporting
confidence: 86%
“…Phytoremediation of soils is generally not viable for Pb because of its strong binding in soils and immobilization in roots of almost all plant species (Nanda Kumar et al 1995). Thus, studies have shown relatively low concentrations of Pb in aboveground tissues of amaranth and other crops grown on slightly Pbcontaminated soils (Mellem et al 2009;Rahman et al 2013). Most of the Pb measured in lettuce grown on heavily Pb-contaminated soil was determined by McBride et al (2013) to be due to contamination of leaf surfaces by soil particles rather than true uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen and P are very important plant macronutrients and their availability in soil as well as their interaction limits plant growth (GROOT et al, 2003). Studies about the effect of biochar on the availability of N in soil have generated many contradictory results varying from positive, negative and even no effect (CLOUGH et al, 2013;RAHMAN et al, 2013;NGUYEN et al, 2017). The same different outcomes are observed during the evaluation of the effects of biochar on plant N absorption (SAARNIO et al, 2013).…”
Section: Soil Sciencementioning
confidence: 99%